Relung Ekologi Burung Hantu (Tyto alba) dan Teknik Pemeliharaannya di Perkebunan Kelapa Sawit (Studi Kasus di PT Unggul Widya Teknologi Lestari) - Aang Kuvaini; . Yulianto; Aprian Saputra (JURNAL CITRA WIDYA EDUKASI, 2021)
Rats are one of the pests of oil palm plantations that are very detrimental, so they must be controlled. The use of Tyto alba is an alternative that can be used to control rat pests biologically, as well as to maintain the balance of the ecosystem in oil palm plantations. The purpose of this study was to determine the ecological niche of Tyto alba and its maintenance techniques in oil palm plantations. The method used in this research is direct observation in the field accompanied by in-depth interviews with key persons who have in-depth knowledge of Tyto alba. The results of the observations were strengthened by literature study and the results were analyzed and evaluated in a descriptive qualitative manner. The results of this study indicate that based on the Food Chain analysis, Tyto alba occupies the top of the food chain so that its existence greatly determines the balance of the ecosystem in oil palm plantations. The maintenance of Tyto alba in oil palm plantations is carried out in Gupon (Owl Cage) which is located in the plantation area, so that Tyto alba is able to adapt from an early age to the conditions of oil palm plantations.